"Attitudes do matter": generic competences in the selection of Business graduates. Issue 1 (16th December 2019) - Charterina, Jon; Pando-Garcia, Julian; Periáñez-Cañadillas, Iñaki
Abstract : Purpose: The purpose of this paper is to determine what competences are considered critical for team and human resources (HR) managers when selecting inexperienced Business graduates. Second, the authors aim to find out differences existing among businesses and organizations according to company size, and very particularly, the resources used with respect to the inexperienced graduate personnel selection practices. Design/methodology/approach: To this end, the authors have performed an empirical study consisting of two qualitative data-gathering processes and a survey. First, the authors completed 12 in-depth interviews, followed by three world cafés with HR managers and consultants. Second, a survey was also conducted with 186 experienced Business graduates, team managers or middle-level staff. Findings: The main results support the idea that generic competencies are the ones most appreciated in graduates. Attitudes are among the generic competencies considered most critical in inexperienced Business graduates. In particular, intra-personal, followed by inter-personal attitudes and values, were the most frequently cited and highly valued competencies. In contrast, most of the specific knowledge competences that are required for Business graduates are taken for granted. For its part, the authors found that excelling inexperienced graduates are those who show convincing proofs of holding attitudinal competences, signaled through some experience of international interchange programs, or pre-graduate internships in companies. Also, the authors found that HR managers and consultants show clear differences of preference for a set of competences or another depending on the size of the recruiting company. In particular, generic competences of knowledge, abilities, attitudes and values rate higher among small firms than larger ones. Originality/value: Finally, the authors give recommendations for faculties and business schools headed to a more intensive development of generic competences, and the learning of skills on how to tailor curricula during studies and how to find jobs.